Geospasial Tingkat Kesempatan Kerja dan Faktor yang Berhubungan dengan Partisipasi Kerja Penyandang Disabilitas Pada Masa Awal Pandemi Covid-19 - Maghfirah Maghfirah (Seminar Nasional Official Statistics, 2022)
Increasing the work participation of disabled people is the 8th goal of the SDGs. However, disable people more risk to lose their work because because they have a greater vulnerability to being affected by covid-19. This study aims to look at the distribution of job opportunity rate of disabled people and their relationship to demographic and socioeconomic characteristics in the early time of covid-19 pandemic. The results showed that the TKK for disabled people was greater in rural areas than in urban areas. Variables that have a significant effect are related to the work participation of disabled people in the formal and informal sectors, namely gender, age, education, training, area of residence, marital status, and severity of disability. Thus, in an effort to increase the opportunities for disabled people to work and stay healthy during the covid-19 pandemic, special support and attention is needed, both in providing facilities and infrastructure and in creating a safe and friendly work environment for persons with disabilities.